Regulation of CD3 expression in a protein kinase C isozyme-deficient T-cell line - KELLEHER, DERMOT P; LONG, AIDEEN (British Society for Immunology, 1993)
Using the T-cell lymphoma line HuT 78, and a clone derived from HuT 78, designated K-4, the role of protein kinase C (PKC) isozymes in the expression of a variety of T-cell surface antigens was investigated. HuT 78 expresses PKC isozymes alpha and beta while K-4 expresses only PKC alpha. Flow cytometric analysis revealed that incubation of HuT 78 cells with phorbol 12-myristate 13-acetate (PMA) results in significant down-regulation of surface expression of CD3. While K-4 cells expressed reduced amounts of CD3, a similar reduction in CD3 expression was not observed when these cells were stimulated with PMA. The regulation of expression of CD11a (LFA-1), CD44, CD45RA and CD45RO and of the class II molecules DR and DP in response to PMA, was similar in both cell lines.
PUBLISHED
Keywords: Clinical Medicine